The Determinants of Tourists’ Intention to Visit Halal Tourism Destinations in Aceh Province - Yusuf, Muhammad Yasir; Innayatillah, Innayatillah; Isnaliana, Isnaliana; Maulana, Hafiizh (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
This present study aims to identify the determinants of tourists’ intention towards halal tourism in Aceh Province. The population of this study was the tourists visiting Aceh Province in 2019 based on the data from the Central Bureau of statistics. The study used a quantitative research method, employing a purposive questionnaire to 300 local tourists and foreign tourists. The study analyzed the data using multiple linear regression with independent variables consisting of perceptions about access, communication, environment, and service. Overall, the study found that the perceptual attributes of access, communication, environment, and service were able to determine the tourists’ intention towards halal tourism in Aceh. The two most dominant determinants in shaping and encouraging increased intention in halal tourism were the Islamic environment and service for halal tourism. The study recommends the importance of adopting the Islamicenvironmental ecosystem and service as a market strategy for halal tourism destinations in Aceh Province.